Low Profile High-gain Antenna for Broadband Indoor Distributed Antenna System - Lu Xu; Yong Jin Zhou, (Applied Computational Electromagnetics Society Journal (ACES), 2020)
Here an improved folded patch antenna with low profile and high gain is proposed. By loading slow-wave metamaterials structure and metal pillars, the antenna operates from 0.6 GHz to 2.1 GHz (111% fractional bandwidth) with the VSWR<2. The profile height is 48.5 mm and 0.095λ at 0.6 GHz. The measured gain is 4 dBi at 0.6 GHz. The average gain is 7.43 dBi over the entire bandwidth. Hence, it is an excellent candidate for the emerging multiband indoor base station application such as 700 MHz, CDMA800, GSM900, DCS1800, PCS1900, UMTS, and IMT2000, etc.